“YouTube as my second classroom”: Indonesian nursing students’ self-regulated language learning on YouTube - Kailani, Ahmad; Suherdi, Didi; Purnawarman, Pupung (JEES (Journal of English Educators Society), 2023)
This study investigated the independent language learning that Indonesian nursing students did after school on YouTube. Six undergraduate nursing students who have a lot of experience with YouTube viewing and have level of English equal to B1 were asked to participate in a one-on-one interview to discuss their opinions of this selfregulated language learning. A narrative inquiry design was deployed to explore the stories of how learners felt about this technologically mediated language learning and how it affected their language skills. The results show that discovering motivation for learning English, searching for extra learning materials, and potential metacognitive learning styles were the three most popular reasons for studying English on YouTube. Students perceived that learning English on YouTube was more flexible, entertaining, and approachable than traditional classroom instruction. However, this informal education does not promote socialization or an awareness of cultural differences between nations. The findings have made a significant contribution to the futureinstructional design of ESP classroom where the integration of YouTube videos may become an alternative for more engaging ESP classroom interaction. Besides, promoting awareness of cultural diversities and appropriate online social interaction need to be considered for YouTube mediated learning activities to help students use the language appropriately within its socio-cultural settings. HIGHLIGHTS: The three most common motivations for nursing students to learn English on YouTube were finding motivation, looking for additional resources, and potential metacognitive learning approaches. The integration of YouTube videos may become an alternative for more engaging ESP classroom interaction. To assist students utilize the language effectively within its socio-cultural settings, YouTube-mediated learning activities need to take fostering awareness of cultural diversity and acceptable online social interaction into account.